Kreativitas Anak melalui Pemanfaatan Limbah Organik sebagai Media Pembelajaran Seni Rupa Berbasis Lingkungan - Aulia Tanzania; Citra Ayu Hidayah; Fidari Nur Dini; Anita Anita (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This program aims to enhance children’s creativity through the utilization of organic waste as an environmentally based visual art learning medium at TK Mujahidah Abung Pekurun. The problem addressed in this program is the limited use of creative learning media that utilize environmental resources and the low level of children’s awareness of the educational value of organic waste. The program employed a descriptive qualitative approach through visual art learning activities integrated with the use of organic waste materials, such as dried leaves, seeds, fruit peels, and twigs. The participants were early childhood students at TK Mujahidah Abung Pekurun. Data were collected through observation of children’s activities, documentation of artworks, and interviews with teachers. The results indicate that the use of organic waste as visual art learning media effectively improves children’s creativity, as reflected in their ability to express ideas, creatively combine materials, and produce diverse and original artworks. In addition, the program increases children’s environmental awareness and introduces early concepts of waste utilization. Therefore, environmentally based visual art learning using organic waste is an effective strategy for developing creativity in early childhood education. Keywords: children’s creativity, organic waste, visual art, environmental-based learning, early childhood education.